NECESIDAD DE PARÁMETROS LEGALES PARA VALORAR LA CONVENIENCIA DE LA EDAD MÍNIMA, A FIN DE NO VULNERAR LOS DERECHOS DEL NIÑO EN EL MARCO DE LAS ADOPCIONES PROHIBIDAS, EN EL CÓDIGO ORGÁNICO DE LA NIÑEZ Y ADOLESCENCIA - Neira Tacure, Kleber René (2015)
This thesis entitled "NEEDS OF PARAMETERS LEGAL TO ASSESS THE SUITABILITY OF THE MINIMUM AGE IN ORDER TO NOT VIOLATE THE RIGHTS OF THE CHILD IN CONNECTION WITH THE ADOPTION” prohibited in the Code of Childhood and Adolescence "is framed in accordance the required institutional guidelines. At present, the legal institution of adoption is primarily aimed at children and adolescents deprived of their family environment; operating as a measure of protection provided by the state and society for them. Despite this, a number of laws do not limit the figure to the adoption of minors, so that Ecuadorian law through Article 165 of the Code of Children and Adolescents provides an adoption process that regulates and sets specific periods in their administrative and judicial phases, which this investigation seeks to determine is the limitation on the age of the children who will be adopted problem currently generated and through which children are deprived of the feeding process called lactation. The problem generated is that adopted children in their first two years of life does not take advantage of breastfeeding which is very beneficial for proper growth and development. In the development of this entire thesis that has been tried it is to encourage people who have already made the tough decision to give up for adoption to their children what then 5 do that they have completed two years old and so they can take advantage of the breastfeeding, then exposing as one of the requirements for adopting the age limit adopted. I counted with an extensive bibliography on the institution of adoption, from doctrinal concepts, legal nature, historical development and a comprehensive analytical and critical study of the rules of the Constitution of the Republic of Ecuador, the Civil Code and the Code for Children and Adolescents, which is vital to the effective realization of the fundamental rights of minors in the state of adoption, just as research was conducted from the point of view of comparative law and reinforced by the conducting field research comprising conducting the interview with lawyers, culminating in the drafting of conclusions and recommendations, as well as the proposed legal reform, thus clearing all the doubts they had about adoption , and as previously said is a vocation to take because you get through it to be parents.